Application of continuous intraoperative neuromonitoring in the study of spinal nerve root thermal injury in a porcine model - Chengxia Wang; Zhuofu Li; Woquan Zhong; Shuai Jiang; Weishi Li (BMC Musculoskeletal Disorders)
Abstract Background A warning system to avoid potential nerve root thermal injury caused by automatic spine robot is essential. However, there is a lack of basic research to support the development of such warning system. The aims of this study are to confirm the feasibility of continuous intraoperative neuromonitoring (CIONM) in spinal nerve root monitoring and study the exposure time of spinal nerve root thermal injury at different temperature in a porcine model. Methods The experiment was carried out on 32 nerve roots of 4 pigs (bilateral L4-S1 nerve roots). Sham group (CIONM only), control group (Room temperature stimulation with CIONM), and 40 °C, 45 °C, 50 °C, 55 °C, 60 °C, 65 °C temperature stimulation groups were conducted at random in each pig. The change of EMG was recorded continuously. The exposure time of nerve root injury at different temperatures was recorded. Histological analysis of the nerve roots was performed to confirm the injury. Results The EMG of the sham, control, 40 °C and 45 °C groups were stable during the experiment, and no significant nerve root injury was observed on histological analysis. The time of 50% EMG amplitude decrease in 50℃, 55℃, 60℃ and 65℃ groups were 277.5 ± 18.2, 59.5 ± 6.2, 20.8 ± 1.0 and 16.5 ± 1.3 s, respectively. And the nerve specimens of these groups showed varying degrees of damage. Conclusions CIONM can be used for continuous monitoring of spinal nerve roots. For 5 min, 40℃ and 45℃ did not cause significant nerve root injury. However, when the temperature reached 50℃ and above, nerve roots appeared injury.